THE TRAINING OF THE SIXTH VERSION ZAHIR ACCOUNTING MICRO,SMALL,AND MEDIUM ENTERPRISE GROUP (MSMe GROUP) IN KADU KEMPONG PADARINCANG VILLAGE, PADARINCANG DISTRICT, IN SERANG REGENCY - Mohamas Husni; Luay Abu Wakas; Robiatul Adawiyah; Goti Gardena Raya; Nurulauliya Hidayanti; Pial Mawadah (Yayasan Education and Social Center, 2023)
Community service activities in the form of Student Work Lectures (KKM) and collaboration with Universitas Bina Bangsa Lecturers regarding optimizing Zahir Accounting Version 6 training in the Micro, Small and Medium Enterprises (MSMEs) group of Kadu Kempong Village, Padarincang, Serang Regency, aim to improve understanding and accounting skills in MSME actors. This study aims to empower MSMEs to manage their finances more efficiently through the use of Zahir Accounting Version 6 software. The method of implementing this activity includes the stages of identifying needs and initial assessment of the MSME group in Kadu Kempong Village. After that, a training program was designed that was adjusted to the level of understanding of the participants. The training focused on introducing the main features of Zahir Accounting Version 6, recording financial transactions, preparing financial reports, and simple analysis. In addition, this activity also includes a question-and-answer session and assistance in applying accounting practices to MSMEs. The results of this activity showed a significant increase in participants' understanding of basic accounting concepts and their ability to use Zahir Accounting Version 6. MSME players are now able to record financial transactions in a more structured manner, produce more accurate financial reports, and are able to analyze the financial health of their businesses. Thus, UMKM Kadu Kempong Village can optimize the use of Zahir Accounting Version 6 software to support their business growth and development. It is hoped that the continuation of this training can assist other MSMEs in overcoming accounting and administrative challenges, as well as potentially boosting the local economy as a whole.